Direct from the COVID-19 crisis : research and innovation sparks in Brazil - Rosa, Mário Fabrício Fleury (2021)
Background The coronavirus disease 2019 (COVID-19) pandemic has spread throughout more than 160 countries, infecting millions of people worldwide. To address this health emergency, countries have organized the flow of production and innovation to reduce the impact on health. This article shows the response of the Brazilian scientific community to meet the urgent needs of the public unified health system [SUS], aiming to guarantee universal access to an estimated population of 211 million. By December 2020, Brazil had recorded more than six million cases and approximately 175,000 deaths. Methods We collected data on research, development and innovation projects carried out by 114 public universities (plus Oswaldo Cruz Foundation [Fiocruz] and Butantan Institute), as reported on their websites. Additionally, we examined the studies on COVID-19 approved by the National Comission for Research Ethics, as well as those reported on the Ministry of Education website as of May 15, 2020. Results The 789 identified projects were classified according to research categories as follows: development and innovation (n = 280), other types of projects (n = 226), epidemiologic research (n = 211), and basic research on disease mechanisms (n = 72). Most proposals focused on the development and innovation of personal protective equipment, medical devices, diagnostic tests, medicines and vaccines, which were rapidly identified as research priorities by the scientific community. Some promising results have been observed from phase III vaccine trials, one of which is conducted in partnership with Oxford University and another of which is performed with Sinovac Biotech. Both trials involve thousands of volunteers in their Brazilian arms and include technology transfer agreements with Fiocruz and the Butantan Institute, respectively. These vaccines proved to be safe and effective and were immediately licensed for emergency use. The provision of doses for the public health system, and vaccination, started on January 17, 2021. Conclusions The mobilized Brazilian scientific community has generated comprehensive research, development and innovation proposals to meet the most urgent needs. It is important to emphasize that this response was only possible due to decades of investment in research, development and innovation in Brazil. We need to reinforce and protect the Brazilian science, technology and innovation system from austerity policies that disregard health and knowledge as crucial investments for Brazilian society, in line with the constitutional right of universal health access and universal health coverage.